Comparison of erectile dysfunction guidelines between the UK (BSSM/NICE) and Europe (EAU). (March 2018) - Rai, Jaskarn; Terry, Tim
Erectile dysfunction is a common and often debilitating condition. The National Institute of Clinical Excellence (NICE) and the British Society of Sexual Medicine (BSSM) in the UK and the European Association of the Urology (EAU) have guidelines on the management of ED. This article will look at the similarities of the guidelines commenting where and how they differ.